Gender differences in the association between anxiety symptoms and thyroid hormones in young patients with first-episode and drug naïve major depressive disorder - Zhao, Ying; Liu, Jia Cheng; Yu, Feng; Yang, Li Ying; Kang, Chuan Yi; Yan, Li Juan; Liu, Si Tong; Zhao, Na; Wang, Xiao Hong; Zhang, Xiang Yang (Frontiers in Psychiatry, 2023)
Objective Gender differences are prevalent in major depressive disorder (MDD), but the gender differences in the relationship between comorbid anxiety and thyroid hormones in young first-episode and drug-naive (FEND) MDD patients are unknown. Methods A total of 1,289 young outpatients with FEDN MDD were recruited. Demographic and clinical data were collected for each patient. The patient’s blood glucose, blood pressure, thyroid hormone, and thyroid antibody levels were measured. The Hamilton depression scale (HAMD), Hamilton anxiety scale (HAMA), and Positive and Negative Syndrome Scale (PANSS) were used to assess patients’ depression, anxiety, and positive symptoms, respectively. Results The prevalence of comorbid anxiety disorders was 80.4 and 79.4% in male and female MDD patients, respectively. Patients with anxiety had higher HAMD and PANSS scores, higher serum thyroid stimulating hormone (TSH), anti-thyroglobulin antibody (A-TG), and thyroid peroxidase antibody (A-TPO) levels, higher blood glucose and blood pressure levels, and more patients with psychotic symptoms and suicide attempts. Male patients were younger and had a younger age of onset. Logistic regression analysis showed that HAMD score and comorbid suicide attempts were significant predictors of anxiety symptoms in both males and females, whereas A-TG predicted anxiety symptoms in female patients only. Limitations: No causal relationship could be drawn due to the cross-sectional design. Conclusion This study showed gender differences in factors associated with anxiety symptoms in patients with MDD. Some factors were associated with anxiety symptoms in both male and female patients, while A-TG was only associated with anxiety symptoms in female patients.